Teologi Pembelajaran Berbasis Ciptaan: Integrasi Ekoteologi, Kecerdasan Buatan, dan Spiritualitas Kristiani dalam Rekonstruksi Pendidikan Agama Kristen Global - Elfin Waruwu; Endirman Tafenao (SANCTUM DOMINE: JURNAL TEOLOGI, 2026)
The main problem addressed is the imbalance between faith, technology, and ecological responsibility in contemporary Christian education, which remains largely anthropocentric and technophobic. The purpose of this research is to formulate a theological foundation and learning model that views creation both nature and technology as a space of revelation and participation in God’s redemptive work. This research employs a qualitative-descriptive method with a theological-philosophical approach through an extensive literature review of the Bible and theological works by Moltmann, Berry, McGrath, and Groome. The findings reveal that integrating eco-theology and AI can expand the dimensions of spirituality toward ecological awareness and digital wisdom, deepening the relationship between humanity, God, and creation. In conclusion, Creation-Based Learning Theology asserts that faith learning is not confined to the classroom but encompasses the entirety of creation and the digital ecosystem as arenas for forming character, ethics, and faithful responsibility within a sustainable global context.